2017
DOI: 10.37358/rc.17.9.5825
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Foliar Boron Fertilization on Chemical Properties and Fatty Acid Compositions of Corn (Zea mays L.)

Abstract: Boron is a member of the metaloid group of elements and is an important essential microelement needed for normal crop growth and development. This research was conducted in 2015 in Hatay (Mediterranean region of Turkey) to determine foliar application of Boron effect on protein ratio, starch ratio and oil yield and oil components of corn. To evaluate the response of foliar application of boron to corn, four boron doses (control, 4, 6 and 8 mg/m 2 ) were applied at the three growing stages (V2; 2 leaves with vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 6 publications
0
8
0
1
Order By: Relevance
“…Barkley et al, 2011, Tang et al, 2013 detected lignoceric acid in peanut oil. The fatty acid composition of oils is significantly influenced by cultivar, ecological conditions, latitude and agricultural practices (Konuskan et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Barkley et al, 2011, Tang et al, 2013 detected lignoceric acid in peanut oil. The fatty acid composition of oils is significantly influenced by cultivar, ecological conditions, latitude and agricultural practices (Konuskan et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Taking previous studies into account, this strategy for supplementing the diet of pasture-fed ewes could have a negative impact on sanogenetic quality of milk fat by decreasing the content in C18:3n-3, c9,t11-CLA and t11-C18:1 (VA, vaccenic acid) [5,6]. In the last years, there is a growing interest for new sources of vegetable oils with high content of unsaturated fatty acids [7][8][9][10][11][12]. Thus, it has been suggested that camelina seeds (Camelina sativa L) should be used as strategy in order to avoid the negative impact on milk FA profile.…”
mentioning
confidence: 99%
“…Boron applications can increase maize yield with low quantities (Güneş et al, 2011). Various studies were performed on boron effects on grain yield of maize, previously (Aref, 2011; Kaur and Nelson, 2015;Horuz and Özcan, 2017;Konuskan et al, 2017, Wasaya et al, 2017Nelson and Meinhardt, 2011). However, insufficient researches were performed on boron effects on hay and silage yields and qualities of maize.…”
Section: Introductionmentioning
confidence: 99%